2019
DOI: 10.22159/ajpcr.2019.v12i2.29646
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Optimization, and Antitumor Activity of L-Asparaginase Extracted From Pectobacterium Carotovorum and Serratia Marcescens on Human Breast Adenocarcinoma and Human Hepatocellular Carcinoma Cancer Cell Lines

Abstract: Objectives: The objective of this research was to obtain isolates capable of producing a high yield of L-asparaginase enzyme and to evaluate the antitumor activity of the purified enzyme against different cancer and normal cell lines. Methods: Isolation of bacteria was performed by the serial dilution technique of soil samples collected from Cairo, Egypt, using modified M9 agar plates. Culture filtrates of selected isolates were quantitatively screened for L-asparaginase production using well-diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Among some products, we can highlight the versatile enzyme L-asparaginase that includes the medical application of its antimicrobial and anti-inflammatory properties besides its use as a chemotherapeutic agent in different cancer cell lines (Abdel-Razik et al, 2019). The strategy of using novel therapeutic agents isolated from S. marcescens has been previously demonstrated in a marine strain with antioxidant and antibacterial activity against some Gram-positive and Gram-negative bacteria.…”
Section: Genes Involved In Antimicrobial Activities or Important Enzymes For Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Among some products, we can highlight the versatile enzyme L-asparaginase that includes the medical application of its antimicrobial and anti-inflammatory properties besides its use as a chemotherapeutic agent in different cancer cell lines (Abdel-Razik et al, 2019). The strategy of using novel therapeutic agents isolated from S. marcescens has been previously demonstrated in a marine strain with antioxidant and antibacterial activity against some Gram-positive and Gram-negative bacteria.…”
Section: Genes Involved In Antimicrobial Activities or Important Enzymes For Industrymentioning
confidence: 99%
“…Both disease and therapy are present in the dual role of S. marcescens in the clinic, responsible for outbreaks (Cristina et al, 2019) was even identified as an opportunist in outbreaks during covid-19 treatment (Amarsy et al, 2020). However, it has shown an extensive presence of enzymes with antimicrobial and anti-inflammatory properties proving effective to even resistant microorganisms and with the possibility of use as a chemotherapeutic agent in different cancer cell lines (Abdel-Razik et al, 2019;Pavithrra & Rajasekaran, 2020).…”
Section: Introductionmentioning
confidence: 99%